Prevailing Cases of Lawyers' Liability in The Conduct of Cases a Case for Prefessional Indemnity - Gasiokwu, Peter Ikechukwu; Ehirim, Ugochukwu Godspower (Yuridika, 2025)
Every profession has peculiar risks and liabilities attaching it. The legal profession and indeed the advocate is not exempt from the prescribed duty of care in his relationship with his clients. This has become so imperative in the face of globalized legal practice in the 21st century that the advocate may bear personal costs in the course of his duty. This article attempts to re-visit the controversy over liability of legal practitioners, particularly litigation lawyers in Nigeria. The common law, as well as the statutory rationale for lawyers' liability is highlighted. A critical analysis of award of costs by the courts on individual lawyers in most recent times is made. Evaluating the trend, it is argued that while a lawyer might be validly liable in the tort of negligence to his client for ‘crass carelessness', imposing prohibitive costs on advocates for daring to push novel or unpopular positions in court, without more, would not help the development of the rule of law in Nigeria. These class of cost orders if enforced religiously against counsel would have the negative effect of keeping victim-lawyers out of practice. In the light of the foregoing, a case is made for mandatory professional indemnity for litigation lawyers to cater for unfortunate costs and to ensure that a lawyer does not compromise his professional ethos for fear of intimidating cost liabilities